Attitude towards preventive dentistry among Iranian senior dental students. - Mr Khami; H Murtomaa; S Razeghi; J I Virtanen (Tehran University of Medical Sciences, 2012)
To investigate attitudes of Iranian senior dental students towards preventive dentistry in relation to their background factors and self-perceived competency in providing preventive care.In spring 2008, a questionnaire survey was conducted with all the senior dental students of seven randomly selected state dental schools in Iran. In addition to the respondents' age and gender, the voluntary questionnaire assessed the students' attitudes towards preventive dentistry by means of a seven-point semantic differential scale of nine qualities and their opposites, and their self-perceived competency in providing preventive care by five separate questions. To identify the underlying dimensions for attitude, a factor analysis with principle component method and varimax rotation was applied. Independent sample t-test served for statistical analysis. Of the 242 students receiving the questionnaire, 182 students (75%) responded. The mean age of the participants was 26 years and 42% of them were men.Based on the factor analysis, which explained 60% of the total variance, two attitude dimensions were identified; the profession-related dimension and the health service-related dimension. Competency in giving preventive care in all the five specified areas was reported by 44% of the students with no significant gender differences. The mean for the dentist-related dimension was significantly higher among the students who reported competency in giving preventive care (P=0.005).There is room for improvement in senior dental students' attitudes towards preventive dentistry. In order to create more positive attitudes for future dental professionals, there should be an early and sufficient exposure to preventive aspects of dentistry in the dental curricula.